التأهيل القيادي في القرآن الكريم يوسف عليه السلام أنموذجًا: دراسة في صناعة القادة = Leadership qualification in the Holy Quran Joseph peace be upon him as a model: a study in the making of leaders - Alshahrani, Mohammed Saeed Ayed; Khaled, Nashwan Abdo (Al-Azhar University, Egypt, 2024)
The research deals with leadership qualification in the Holy Quran through the story of the Prophet of God, Joseph - peace be upon him - and the problem of the research is to benefit from the Quranic model represented by Joseph - peace be upon him - through the Quranic verses mentioned in his story. The research aims to highlight the stages of discovering leadership elements, sources of forming a leadership personality, and the qualities and characteristics of a successful leader, through the story of Joseph - peace be upon him - relying on the deductive approach; The study reached a number of results, the most important of which are: planning and wise leadership are the basis for every success, getting out of crises and tribulations, and advancing the country towards progress and prosperity. The objectives of this study include: deducing the mechanisms of leadership qualification in the Holy Quran through the story of Joseph - peace be upon him - and highlighting the most important factors for qualifying the leadership personality. And knowing the features and characteristics of divine leadership in the Prophet of God Joseph - peace be upon him.